Design Strategy of Quantum Dot Thin‐Film Solar Cells. Issue 45 (20th October 2020) - Kim, Taewan; Lim, Seyeong; Yun, Sunhee; Jeong, Sohee; Park, Taiho; Choi, Jongmin
Abstract: Quantum dots (QDs) are emerging photovoltaic materials that display exclusive characteristics that can be adjusted through modification of their size and surface chemistry. However, designing a QD‐based optoelectronic device requires specialized approaches compared with designing conventional bulk‐based solar cells. In this paper, design considerations for QD thin‐film solar cells are introduced from two different viewpoints: optics and electrics. The confined energy level of QDs contributes to the adjustment of their band alignment, enabling their absorption characteristics to be adapted to a specific device purpose. However, the materials selected for this energy adjustment can increase the light loss induced by interface reflection. Thus, management of the light path is important for optical QD solar cell design, whereas surface modification is a crucial issue for the electrical design of QD solar cells. QD thin‐film solar cell architectures are fabricated as a heterojunction today, and ligand exchange provides suitable doping states and enhanced carrier transfer for the junction. Lastly, the stability issues and methods on QD thin‐film solar cells are surveyed. Through these strategies, a QD solar cell study can provide valuable insights for future‐oriented solar cell technology. Abstract : Quantum dot thin‐film solar cell has attracted great attention with room for improvement. To achieve high‐efficiency commercial photovoltaic devices, appropriate optical and electrical designs are needed to breakdown the current limitation of quantum dot solar cells. Furthermore, recent approaches for stability and eco‐friendly issues in terms of both materials and structures are discussed.